A practical method for seismic response analysis of nonlinear soil-structure interaction systems. Issue 10 (July 2021) - Huang, Caigui; Gu, Quan; Huang, Surong
Soil–structure interaction (SSI) plays an important role in the analysis of seismic structural responses. This study significantly extends an efficient linear SSI analysis method presented previously by the authors and co-workers to realistic nonlinear SSI systems, that is, systems with nonlinear soil, nonlinear structures, and flexible foundations (e.g. single- or multiple-pile foundations). The flexible foundations lying on half-space nonlinear soil are represented by frequency-dependent compliance functions that are fitted numerically instead of obtained by closed-form solution. These functions are then transferred to the time domain using the discrete-time recursive filtering method. A non-iterative algorithm is applied to guarantee the boundary conditions between soil and structure, that is, the displacement continuity and force equilibrium between them. The proposed method is implemented on an open-source FE software framework, called OpenSees. The accuracy and efficiency of the extended coupling method are investigated in detail through the seismic response analyses of typical soil–foundation–structure systems while considering the cases of linear or nonlinear soil, linear or nonlinear structures, and single- or multiple-pile foundations. Results show that the extended coupling method is significantly faster than the traditional FE method and provides acceptably accurate solutions for SSI systems with linear or low-to-moderate nonlinear soil. The paper provides a method for fast evaluation of nonlinear SSI effects in seismic structural response analysis.